Infestation of pine (Pinus sylvestris L.) seedlings with the pinewood nematode Bursaphelenchus xylophilus Steiner and Buhrer (Nickle) through wood sawdust - Elena N. Arbuzova; Oleg A. Kulinich; Andrey A. Chalkin; Natalia I. Kozyreva; Vyacheslav V. Gorbach; Alexander Yu. Ryss (Annals of Forest Science, 2023)
Abstract Key message There are various pathways for infesting pine trees with the pinewood nematode (PWN), Bursaphelenchus xylophilus. As a result of the experiment, we determined that sawdust infested with the nematode can pose a phytosanitary risk. Nematodes actively moved from infested sawdust into root or stem damaged pine seedlings. Context The spread of PWN, Bursaphelenchus xylophilus in pine plantations and forests is caused by beetles of the genus Monochamus, but the nematode can also be introduced via different coniferous commodities. Aims The study objective was to assess the possibility that injured roots and stems of Pinus sylvestris seedlings could be infested with PWN through nematode-infested sawdust. Methods Experiments of PWN infestation of pines were conducted in a climatic chamber at a temperature of 26 °C and moisture content of 60–70%. After a month in the climatic chamber, the seedlings were exposed to PWN through infested sawdust. Results It was determined that PWN actively penetrated seedlings with injured stems when directly exposed to PWN-infested sawdust (83% of seedlings (p < 0.012)). Similar results were obtained in the trial in which during planting, seedlings with damaged roots were exposed to PWN infested sawdust (50% of seedlings (p < 0.008)). The nematodes could not infest seedlings if the sawdust occurred on the soil surface at a distance of 2.5 cm from the seedling stem. Conclusion Our results indicate nematode infestation of pine trees can occur through PWN-infested sawdust.